LOOKING FOR QUR’AN TEACHER WITH THE HAVERSINE FORMULA METHOD - A. MUHAMMAD SYAFAR; RIDWAN A. KAMBAU; NURUL HIKMAH MULYANAH (Journal of Information Technology and Its Utilization, 2021)
Education to read and write the Qur'an is the most important thing in Muslim life. The problem that arises is the difficulty of getting a schedule fit between prospective Koran teachers and students, besides the lack of places to study the Koran for adults is also a problem that should be a concern for the sake of the ongoing process of learning the Qur'an.The research method used in this study is a qualitative research method with an experimental approach for programming methods using the Haversine Formula method. The results of this research are in the form of the development of Private Recitation Service and Report Applications Using the Android-Based Haversine Formula Method which can be used to facilitate the community in the process of searching for private Using the Haversine Formula Method Based on Android with distance calculation accuracy rate is 98.92%